Estudo da ultraestrutura mitocondrial de eosinófilos humanos imaturos, maduros e na síndrome de hipereosinofilia - Cinthia Palazzi Miranda da Silva (2021)
Eosinophils are immune cells classically involved in allergic and infectious diseases caused by helminths. More recently, the eosinophil was recognized as a multifunctional granulocyte for its role in several processes such as antigen presentation, immunoregulation, maintenance of homeostasis, development and regulation of organs and tissues and fibrosis. Eosinophils pre-synthesize dozens of proteins and store them in secretory granules, called specific granules, which exhibit unique morphology in terms of their ultrastructure.Several aspects of the secretory pathway of these cells are already elucidated in immune responses. However, little is known about the population of mitochondria, their dynamics and structural organization during the eosinophil development and maturation and in the context of eosinophilic diseases. In the present work, the ultrastructural features of mitochondria were studied during the maturation process of human eosinophils in cultures and in response to the human hypereosinophilic syndrome (HES), a disease characterized by eosinophilia in both peripheral blood and tissues. Samples of immature and mature eosinophils from cultures as well as eosinophils isolated from blood and biopsies (skin) from HES patients were processed by transmission electron microscopy (TEM). Different aspects were quantitatively and quantitatively evaluated in electromicrographs such as: area, number, circularity and mitochondria cristae pattern, as well as the occurrence of interaction with other organelles. Our results showed that during the maturation process of human eosinophils, their mitochondria population is drastically reduced. Both the number and the average mitochondrial area are reduced by 50% when immature cells are compared to mature cells in cultures. In addition, the maturation process of human eosinophils leads to a significant reduction in the cristae number (P <0.05). In mature eosinophils from patients with HES, the number and area of mitochondria, as well as the pattern of the cristae of these organelles, differs depending on where they are located. Although circulating eosinophils have a larger population of mitochondria and a predominance of lamellar ridges compared to tissue eosinophils, they show a pattern of ridges called mixed, which consists of tubular and lamellar pattern.Considering that the mitochondrial cristae are closely associated with the metabolism / functional activity of these organelles, these data demonstrate that the eosinophil mitochondrias respond to the tissue microenvironment with morphological changes in their cristae. In addition, ultrastructural analyses revealed a close interaction between mitochondria and other organelles, particularly with specific granules, both immature and mature, and lipid droplets. Mitochondria seem to influence the granulogenesis process, since 45% of the entire mitochondria population established contact with granules. Altogether, our data indicate that eosinophil mitochondria play an important role in the granulogenesis process and respond to the cell microenvironment with structural changes and interactions with other organelles. Our findings reinforce the role of mitochondria as multifunctional organelles in cells of the immune system.